2018
DOI: 10.3390/atmos9020057
|View full text |Cite
|
Sign up to set email alerts
|

Personal Exposure to PM2.5 in the Megacity of Mexico: A Multi-Mode Transport Study

Abstract: Recurrent personal exposure to ambient PM 2.5 is associated with adverse human health effects, in particular on the respiratory and cardiovascular systems. Here, we present an assessment of personal exposure and inhalation of PM 2.5 for five modes of transport (walking, cycling, public bus (trolleybus and diesel bus), conventional car (CC) and hybrid-electric car (HEC)) and two routes of similar distance, along a major road in the Mexico City metropolitan area (MCMA). Arithmetic average exposure concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…This evolution is a driving force in the research field on cyclists' exposure to air and noise pollution. Thus, new tools have been made accessible to researchers to address new research goals like estimating the difference in exposure for similar trips according to the transport mode [9,26], measuring the short term health impact of cyclists' exposure to air pollution [27], or modelling and predicting cyclists' exposure in urban environments [18][19][20]28,29].…”
Section: The Development Of Low-cost Sensors: New Paradigm and Opportmentioning
confidence: 99%
“…This evolution is a driving force in the research field on cyclists' exposure to air and noise pollution. Thus, new tools have been made accessible to researchers to address new research goals like estimating the difference in exposure for similar trips according to the transport mode [9,26], measuring the short term health impact of cyclists' exposure to air pollution [27], or modelling and predicting cyclists' exposure in urban environments [18][19][20]28,29].…”
Section: The Development Of Low-cost Sensors: New Paradigm and Opportmentioning
confidence: 99%
“…In their study, Hernandez-Paniagua et al [34] used boxplot analysis to highlight the statistical values of pollutant emissions, comparing emissions from urban areas with diesel bus transportation with emissions from areas with trolleybus transportation (electric propulsion system).…”
Section: Diesel Bus Monitoring Data Analysismentioning
confidence: 99%
“…The event was considered as an anomaly that would have skewed the averaged concentrations. However, it indicates a higher susceptibility of cyclists to such extreme pollution on-road events that can commonly occur on congested routes in urban areas (Hernández-Paniagua et al 2018). Other studies have also reported that cyclists are in the most vulnerable position in terms of traffic pollution exposure (Chaney et al 2017) where it was estimated that an hour of cycling in Delhi during MP caused 40% higher PM2.5 inhaled dose than an entire-day's dose in cities like Tokyo, London and New…”
Section: Modal Concentrations Variationsmentioning
confidence: 99%
“…(2020) reported that PM2.5 exposure concentrations for walking and cycling were quite similar and were notably higher than for bus and car. Several studies concluded that the largest exposure to PM2.5 was observed during cycling; however, the route choice can reduce exposures by 15-75% (Ham et al, 2017;Hernández-Paniagua et al, 2018). It was clear from these studies that fixed-site monitoring did not properly reflect personal exposure, especially during heavy traffic times, where PM2.5 levels are significantly influenced by the mode of travel (Frey et al, 2020;Huang et al, 2012;Kaur and Nieuwenhuijsen, 2009;Qiu et al, 2017).…”
mentioning
confidence: 99%